The Lost Throne of Queen Hetepheres from Giza: An Archaeological Experiment in Visualization and Fabrication - Der Manuelian, Peter.
In 1925, one of the greatest discoveries made at Giza revealed a small, unfinished chamber (labeled “G 7000 X”) more than twenty-seven meters underground, just east of the Great Pyramid. The Harvard University–Boston Museum of Fine Arts Expedition found there the deteriorated burial equipment, sarcophagus, and other objects belonging to Queen Hetepheres I, presumed consort of Snefru and mother of Khufu. Since the discovery of this rare Old Kingdom royal assemblage, the thousands of small fragments have remained in storage in the Egyptian Museum, Cairo. Meticulous documentation allowed the excavators to reconstruct some of the queen’s furniture. However, the most exquisite piece, her “second” chair or throne, made of cedar with hundreds of faience inlays and completely gilded, was never reconstructed. This paper describes an interdisciplinary collaboration initiated by the Giza Project at Harvard University to create a full-scale reproduction of Hetepheres’s second chair in modern cedar, faience, gold, gesso, and copper. The goals for this visualization experiment were to reconstruct the excavation history, the iconography, and to document, insofar as possible, the ancient workflow the Egyptians used to construct this Old Kingdom masterpiece. The final results produced a new museum display object and research/teaching tool. doi: http://dx.doi.org/10.5913/jarce.53.2017.a001